Polimorfisme Gen Sitokrom P450 2A6 Alel *1, *4, *7 dan *9 pada Subyek Uji Perokok Suku Thionghoa Indonesia - Patramurti, Christine; Candaya, Evan Julian; Kiatarto, Stella Felina; Karut, Agnes Kurniati (Jurnal Farmasi Indonesia, 2019)
The CYP2A6 gene, encodes the CYP2A6 enzyme, has a highly polymorphism. These ezyme have played a role in nicotine metabolism, one of the active compounds in cigarettes that causes of cigarette dependence. The active form of the CYP2A6 gene allele is * 1 allele and some inactive forms of the CYP2A6 gene allele are * 4, * 7 and * 9 alleles. The inactive alleles would reduce the activity of the CYP2A6 enzyme. The genotypes of CY2A6 gene (CYP2A6* 1, * 4, * 7 and * 9) among Chinese Indonesian smokers were determined by allele-specific polymerase chain reaction (PCR) followed by electrophoresis method. The cigarette dependence was analyzed using the Fagerstrom Test for Nicotine Dependence (FTND) method.This study showed that there are CYP2A6 polymorphism genes among 30 smokers who participate in these study. The frequencies of the genotypes of CYP2A6 alleles were CYP2A6 *1/*1 (46.7%), CYP2A6 *1/*4 (16.7%), CYP2A6 *1/*7 (3.3%), CYP2A6 *1/*9 ( 10%), CYP2A6 *1/*4/*7 (6.7%), CYP2A6 *1/*4/*9 (10.0%), CYP2A6 *1/*7/*9 (3.3% ) and CYP2A6 *4/*7/* 9 (3.3%). The presence of inactive alleles can reduce the activity of the CYP2A6 enzyme in metabolizing nicotine, which can reduce the effects of cigarette dependence. The CYP2A6 gene, encodes the CYP2A6 enzyme, has a highly polymorphism. These ezyme have played a role in nicotine metabolism, one of the active compounds in cigarettes that causes of cigarette dependence. The active form of the CYP2A6 gene allele is * 1 allele and some inactive forms of the CYP2A6 gene allele are * 4, * 7 and * 9 alleles. The inactive alleles would reduce the activity of the CYP2A6 enzyme. The genotypes of CY2A6 gene (CYP2A6* 1, * 4, * 7 and * 9) among Chinese Indonesian smokers were determined by allele-specific polymerase chain reaction (PCR) followed by electrophoresis method. The cigarette dependence was analyzed using the Fagerstrom Test for Nicotine Dependence (FTND) method.This study showed that there are CYP2A6 polymorphism genes among 30 smokers who participate in these study. The frequencies of the genotypes of CYP2A6 alleles were CYP2A6 *1/*1 (46.7%), CYP2A6 *1/*4 (16.7%), CYP2A6 *1/*7 (3.3%), CYP2A6 *1/*9 ( 10%), CYP2A6 *1/*4/*7 (6.7%), CYP2A6 *1/*4/*9 (10.0%), CYP2A6 *1/*7/*9 (3.3% ) and CYP2A6 *4/*7/* 9 (3.3%). The presence of inactive alleles can reduce the activity of the CYP2A6 enzyme in metabolizing nicotine, which can reduce the effects of cigarette dependence. The CYP2A6 gene, encodes the CYP2A6 enzyme, has a highly polymorphism. These ezyme have played a role in nicotine metabolism, one of the active compounds in cigarettes that causes of cigarette dependence. The active form of the CYP2A6 gene allele is * 1 allele and some inactive forms of the CYP2A6 gene allele are * 4, * 7 and * 9 alleles. The inactive alleles would reduce the activity of the CYP2A6 enzyme. The genotypes of CY2A6 gene (CYP2A6* 1, * 4, * 7 and * 9) among Chinese Indonesian smokers were determined by allele-specific polymerase chain reaction (PCR) followed by electrophoresis method. The cigarette dependence was analyzed using the Fagerstrom Test for Nicotine Dependence (FTND) method.This study showed that there are CYP2A6 polymorphism genes among 30 smokers who participate in these study. The frequencies of the genotypes of CYP2A6 alleles were CYP2A6 *1/*1 (46.7%), CYP2A6 *1/*4 (16.7%), CYP2A6 *1/*7 (3.3%), CYP2A6 *1/*9 ( 10%), CYP2A6 *1/*4/*7 (6.7%), CYP2A6 *1/*4/*9 (10.0%), CYP2A6 *1/*7/*9 (3.3% ) and CYP2A6 *4/*7/* 9 (3.3%). The presence of inactive alleles can reduce the activity of the CYP2A6 enzyme in metabolizing nicotine, which can reduce the effects of cigarette dependence.